PENGARUH TERAPI MUSIK KOREAN POP TERHADAP TINGKAT STRES SISWA SMKN 1 KABUPATEN TANGERANG - Dwi Amalia Susanti; Tuti Wahyuningsih; Lastri Mei Winarni (Nusantara Hasana Journal, 2022)
Stress is the nonspecific response of the body to any demand. An individual may be said to have experienced stress when the individual experiences a state or condition that exists within him due to various demands that come from within him or from his environment. One method of reducing stress is music therapy. The music used in therapy is Korean Pop music. The purpose of the study was to find out whether or not Korean Pop music therapy has an effect on decreasing the stress level in students at Vocational High School 1 Kabupaten Tangerang. The method uses a Quasi Experimental design with a pre-test post-test control group design. The population in this study is class XII students majoring in Cooling and Air Conditioning Engineering as many as 71 respondents including class XII TPTU 1 and class XII TPTU 2. Sample collection technique with total sampling. The instrument used is a DASS 42 questionnaire sheet. The results of the analysis used were univariate and bivariate analysis using the Wilcoxon Rank Test were found to have the effect of Korean Pop music therapy on student stress reduction as evidenced by its significance of 0.000 where < 0.05 means there is an effect.